Benefits in environment-related measures for company due to EMS implementation - Lau, Hau Yee; Ku Samsu, Ku Noor Syazana; Abdul Kadir, Muhamad Nazmie; Abdulmottaleb Elgadi, Ahmed; Alias, Mohamad Fakhrul Zahin (Penerbit UTHM, 2020)
In the urban development, Environmental Management System (EMS) is known as a standardization of working system that thoroughly considered environmental improvement by the management of environmental data and information in the company. In line with that, this chapter is aimed to discuss the benefits of ISO 14001 between two differences companies, which are certified and non-certified in finding the possible solutions in order to maintain the highest quality of environmental in industry. As the ISO 14001 certificate holder, the particular organization such as Corporation Commission of Malaysia (SMM) can improve their environmental performance by top management commitment. Thus, the cost savings can be achieved through the improvement of energy consumption and waste minimization. Other than that, the implementation of ISO 14001 also reduced the risk of pollution incidents and other releases to the environment which helps a lot in finance of that company.